Mexican-National Institute of Neurology and Neurosurgery-Stroke Registry: Results of a 25-Year Hospital-Based Study - Arauz, Antonio; Marquez-Romero, Juan Manuel; Barboza, Miguel A.; Serrano, Fabiola; Artigas, Carol; Murillo-Bonilla, Luis Manuel; Cantú-Brito, Carlos; Ruiz-Sandoval, José Luis; Barinagarrementeria, Fernando (Frontiers in Neurology, 2018)
Background and Purpose: Stroke has been scarcely studied in Latin America (LA). The Mexican Institute of Neurology Stroke Registry was established in 1990 as a prospective computer-based database to register data obtained from patients admitted with stroke. Using this data, we attempted to define the profile of risk factors and outcomes. Methods: The demographic data, stroke description, ancillary tests, vascular risk factors, and modified Rankin scale (mRs) were registered. Ischemic stroke subtyping was based on the TOAST classiﬁcation. We followed-up patients using multiple overlapping methods. Primary outcomes included mRs, recurrence and death at 30-days and at the end of follow-up. Results: We included 4,481 patients with a median follow-up of 27 months, (17,281 person-years follow-up). The mean age was 52.8±18 years. There were 2,229 males (50%) included in the study. CI was present in 64.9%, intracerebral hemorrhage (ICH) in 25.6% and cerebral venous thrombosis (CVT) in 6.3%. Hypertension was the major risk factor (46.5%). The most common cause of CI was atherosclerosis (27%). ICH was mainly hypertensive (58%), and 60% of CVT were puerperal. Overall, the mortality rate was 24.5%. The recurrence rate was 16.9%. Poor outcome (mRs>3) was found in 56.2% of patients. The best outcomes were observed in CVT patients (74.5% mRs≤2), whereas 72.1% ICH patients had mRs≥3. Conclusions: This is one of the largest hospital-based registries in LA and shows significant differences with other previously published registries, including a younger age, relatively less hypertension, and larger proportion of CVT. Poor functional outcome was common. This study adds to the understanding of geographic differences in stroke characteristics and outcomes.